PENGARUH JAMINAN SOSIAL TENAGA KERJA, DISIPLIN KERJA DAN KOMITMEN ORGANISASI TERHADAP PRODUKTIVITAS KARYAWAN - Wujud Ahsan Hidayatullah; Muhammad Mansur; Afi Rahmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThis study aims to test and analyze the Effect of Social Security, Work Discipline and Organizational Commitment on Productivity of Production Section Employees at PT. INDONESIA BIOTECH GUARANTEE Probolinggo City both partially and simultaneously. In this study the population amounted to 40 employees and all were taken as samples. “Data collection through questionnaires, data analysis in this study using SPSS version 25. The sampling technique uses quantitative methods, while the data testing techniques used in this study include validity test, reliability test, classic assumption test, multiple linear regression analysis, and testing the research hypothesis”. The results of the analysis show that partially or simultaneously social security, work discipline and organizational commitment have a positive and significant effect on employee productivity at PT. NONGGUAN BIOTECH INDONESIA City of Probolinggo.Keywords: Social Security, Work Discipline, Organizational Commitment and Employee Productivity